Simplified MS2 phage-like particle production including a novel maturation protein internal fusion affinity tag - Enos C. Kline; Rose Duong; Qin Wang; Barry R. Lutz (Biotechnology & Biotechnological Equipment)
Phage-like particles (PLPs) are fabricated self-assembling nanoparticles derived from the structural elements of bacteriophages. These particles have biotechnological utility because of the ability to easily modify surface chemistry and compartmentalize nucleic acids or other materials. A consequential implementation of PLPs in diagnostics is as process controls in nucleic acid amplification tests, where control RNAs are packaged within the protein capsid and protected from degradation by RNases in the sample matrix. Key developments in PLP controls have enhanced the packing efficiency of RNAs into particles, reduced the complexity of their plasmid expression systems, and shifted purification from ultracentrifugation to affinity chromatography, producing progressively greater yields with higher purity. Expanding on prior improvements, this study establishes a revised set of plasmid vectors for Emesvirus zinderi (MS2) derived PLPs that streamline vector manipulations for rapid prototyping of new particles, provide validation of an alternative affinity tag for purification, and contributes a high-throughput low-volume spin column purification strategy. These advancements are combined with a novel internal fusion site in MS2 maturation protein A, a passive element of the MS2 capsid in prior PLP designs, that is capable of displaying polypeptides on the particles’ surface. The functionality of the chimeric maturation protein’s surface display is verified with an affinity tag fusion and subsequent purification. This advancement increases the number of available peptide display sites for the MS2 PLP platform with wide-ranging implications for future applications.